Engineering Silkworms for Resistance to Baculovirus Through Multigene RNA Interference - Subbaiah, Edupalli V. (Genetics Society of America, 2013)
Bombyx mori nucleopolyhedrovirus (BmNPV) that infects the silkworm, B. mori, accounts for >50% of silk cocoon crop losses globally. We speculated that simultaneous targeting of several BmNPV essential genes in transgenic silkworm would elicit a stable defense against the virus. We introduced into the silkworm germline the vectors carrying short sequences of four essential BmNPV genes in tandem, either in sense or antisense or in inverted-repeat arrangement. The transgenic silkworms carrying the inverted repeat-containing transgene showed stable protection against high doses of baculovirus infection. Further, the antiviral trait was incorporated to a commercially productive silkworm strain highly susceptible to BmNPV. This led to combining the high-yielding cocoon and silk traits of the parental commercial strain and a very high level of refractoriness (>75% survival rate as compared to <15% in nontransgenic lines) to baculovirus infection conferred by the transgene. We also observed impaired infectivity of the occlusion bodies derived from the transgenic lines as compared to the wild-type ones. Currently, large-scale exploitation of these transgenic lines is underway to bring about economic transformation of sericulture.